Identification of genetic variants in two Vietnamese patients with hypertrophic cardiomyopathy by Whole exome sequencing - Lien, Nguyen Thi Kim; Van Tung, Nguyen; Trong Tu, Le; Van, Dang Thi Hai; Nga, Vu Quynh; Lan, Nguyen Ngoc; Hien, Nguyen Thanh; Thanh, Le Tat; Duc, Nguyen Minh; Hoang, Nguyen Huy (Vietnam Journal of Biotechnology, 2024)
Hypertrophic cardiomyopathy (HCM) is a common genetic cardiovascular disease and a major cause of sudden death. It is also involved with increased morbidity and mortality of various cardiovascular diseases. Genetic factors have been identified as playing an important role in determining the phenotypic manifestation of cardiac hypertrophy. However, only 50–60% of HCM patients have been identified as having mutations in known genes, suggesting that studies are needed to find more disease genes. HCM is an autosomal dominant disorder caused by mutations in genes encoding for sarcomeric proteins and proteins involved in many cardiomyocyte signaling pathways that activate protein tyrosine kinases. The role of specific protein tyrosine phosphatases (PTPs) in these pathways is unknown. Advances in next-generation sequencing (NGS) technology allow the application of genetic analysis-based diagnostics to become more widespread and help differentiate HCM from other cardiomyopathies. The results of genetic diagnosis will provide insights into the cell biology and pathogenesis of HCM as a basis for developing therapies that can prevent or treat patients.In this study, whole exome sequencing was performed on two patients who were diagnosed with HCM to screen the associated mutations. Two heterozygous mutations c.836A>C, p.Tyr279Ser and c.83A>C, p.His28Pro have been identified in the PTPN11 and PRKAG2 gene, respectively. These results have provided an understanding of the cause of the patient’s disease, helping clinicians diagnose and provide genetic counseling to the patient's family.